Evaluation of mechanical properties of three commonly used suture materials for clinical oral applications: an in vitro study - Saquib Abullais, Shahabe; Al-Qahtani, Nabeeh Abdullah; Naqash, Talib Amin; Khan, Abdul Ahad; Arora, Suraj; Bhavikatti, Shaeesta (Vojnosanitetski pregled, 2022)
Background/Aim. Appropriate selection of suture materials is a crucial step in oral, maxillofacial and periodontal surgery for uneventful healing. We have scarcity of comprehensive studies comparing mechanical properties of commonly used suture material in oral surgery. The present in vitro study sought to evaluate the effect of saliva on the strength, elongation and stiffness of the commonly used suture material over a period of two weeks. Methods. Three suture materials, silk (SL), polyglactin 910 (PG) and polypropylene (PP), were used in 4–0 gauge. A total of 120 suture samples (40 from each material) were used for the investigation. Artificial saliva was mixed with human serum in 1:1 ratio and maintained at pH of 7.4 to 8.1 to simulate oral environment. All samples were tested at pre-immersion (baseline), as well as on the 3rd, 7th and 14th day in the post-immersion period. A universal testing machine was used to test the selected mechanical properties. The collected data were subjected to statistical analysis. Results. The distribution of mean baseline strength and percentage elongation was significantly higher in the PP group (p < 0.001), whereas stiffness score was the highest in the SL group (p < 0.001). Inter-group comparison revealed that the PP group had maximum tensile strength compared to the PG and SL groups at all time points. When percentage elongation was compared, the PP and PG groups showed the highest values on the 7th and 14th day, respectively. The PP group exhibited the highest stiffness values compared to the SL and PG groups on the 7th and 14th day in the post-immersion period (p < 0.001). Intra-group comparison showed that all suture materials had significant difference in mechanical properties when pre-immersion values were compared to the 14th day post-immersion values (p < 0.001). Conclusion. PP sutures are the strongest and have the highest tensile strength and elongation property. PP seems to sustain its tensile strength better than SL and PG at the end of the 14th day. Controlled clinical studies are necessary to verify this finding in an in vivo setting.
Keywords: materials testing; polymers; polypropylenes; saliva, artificial; silk; sutures; tensile strength